INNOVATIVE TECHNOLOGIES DURING THE TRAINING OF YOUNGER SPECIALISTS (Innovative professional education, 2023)
The article analyzes innovative approaches to the training of applicants for vocational pre-higher education in Ukraine. The need for innovative approaches of personal-oriented cooperation between the teacher and the student of education is revealed.
Keywords: innovative pedagogical technologies, innovations, competence, vocational higher education